Risk-based Approach in Obtaining and Analysing the Characteristics of Baikal Skullcap Suspension Cultures - A. A. Shmarova; N. S. Pivovarova; O. N. Abrosimova (Разработка и регистрация лекарственных средств, 2022)
Introduction. The use of biologically active compounds of Baikal skullcap (Scutellaria baicalensis Georgi) becomes especially important under pandemic conditions. The plant's value becomes the cause of overexploitation of the skullcap subterranean parts, which leads to the reduction of the population distribution range and inappropriate conditions of collection and harvesting. To prevent the extinction hazard of the species, in vitro cultivation of the plant's cells becomes a promising technology. This opens up the prospect of studying the physiology and biochemistry of plant cells, regulating the direction of valuable secondary metabolites synthesis and creating medicines without interfering with the natural habitat. Modern technologies provide opportunities to automate cell cultivation in order to minimize human involvement in the process. However, cultivation of plant cells is a probabilistic process that is influenced by a range of factors. The use of risk management tools will reduce the number of unintended consequences leading to dangerous and critical cell culture conditions.Aim. Risk analysis resulting from in vitro cultivation of Baikal skullcap (Scutellaria baicalensis Georgi).Materials and methods. The object of the study was suspension cultures of Scutellaria baicalensis obtained from loose plant callus. Suspensions of Scutellaria baicalensis cells were grown in 250 ml flat-bottomed conical flasks under conditions of constant mixing on a shaker (rotation speed 100 rpm). The subculture cycle was 21 days. For microscopy of cell biomass, we used 0.1 % neutral red (NK) and 0,025 % Evans blue (EG) solution. Process risks were assessed using a cause-and-effect diagram (Ishikawa diagram).Results and discussion. It was found that the cells in the suspension cultures of skullcap were characterized by an elongated oval shape. Primary suspensions were distinguished by the presence of predominantly parenchymal cells (70 ± 2,0 %). A large aggregation was observed in the primary suspensions. The diameter of the aggregates reached about 8–15 mm. The growth properties of Baikal skullcap suspension depended on the density of the inoculum. As the amount of transplanted biomass decreased, cells showed a tendency to destruction. The results indicated the need for risk analysis of the laboratory technology of Baikal skullcap suspension cultivation. Five most important factors in plant cell cultivation were identified: callus quality, quality of prepared liquid nutrient medium, equipment serviceability and suitability, operator actions, and suitability of cell culture technology and biomass viability index sampling.Conclusion. An algorithm for analyzing the security of a Baikal skullcap suspension culture is proposed. The risk assessment can be used to make a conclusion about the probability of undesirable effects and their impact on the process. Risk management tools provide the basis for modernization of the available technology and automatic outfitting of the process.